PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL - Syarifudin, Syahrul; Nuriah, Sri; Yusuf , Ayus Ahmad (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2023)
The purpose of this Study was to analyze and obtain empirical facts about Firm Size, Leverage, Profitability an Firm Age. Teh population in this Study is the annual report and financial statements of the High-IC Intensive Industries Companies Listed on the Indonesia Stock Exchange in 2017-2021 as many as 201 companies. The sampling technique use is purposive sampling. So that the sample in this study amounted to 68 companies as many as 340 observational data. The method used is descriptive and verification method with quantitative data. Data collection techniques using observations don't participate. The analysis technique used in this study is descriptive analysis, classic assumption test, panel data regression analysis, coefficient of determination and hypothesis testing using the Eviews Ver. 9.0 application program. Hypothesis testing shows that Firm Size, Leverage, Probability and Firm Age jointly influence the Intellectual Capital Disclosure. Firm Size, Leverage and Probability partially has a significant positive effect on Intellectual Capital Disclosure. Firm Age partially has a significant negative effect on Intellectual Capital Disclosure.